UPAYA MENINGKATKAN KETERAMPILAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI MELALUI METODE DRILL PADA SISWA KELAS XII-3 SMA NEGERI 7 KEDIRI - Dony Prasetyo; Budiman Agung Pratama; Miftahkodin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Herefore, this study aims to examine the effectiveness of the drill method in improving students' underhand passing skills.This study employs Classroom Action Research (CAR) with a quantitative approach. The research subjects consist of 34 students from Class XII-3 at SMA Negeri 7 Kediri. Data were collected through pretest and posttest assessments of underhand passing skills before and after the implementation of the drill method. Data analysis techniques include the Paired Sample t-Test to measure students’ skill improvement. The results indicate that the drill method significantly impacts the improvement of underhand passing skills. Statistical analysis reveals a significant difference between pretest and posttest scores, with an average increase of 2.44 points. Additionally, the correlation between pretest and posttest scores shows a strong relationship, with a correlation coefficient (r) of 0.649 and a significance value of 0.000 (p < 0.05).The conclusion of this study is that the drill method is effective in enhancing students' underhand passing skills. Repetitive training enables students to refine their techniques, improve movement coordination, and boost their confidence in playing volleyball. Therefore, the drill method is recommended as an effective training strategy for volleyball instruction in schools.